English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-26 13:22:28 · 15 answers · asked by noggle4 2 in Science & Mathematics Mathematics

15 answers

even integers= 2x+(2x+2)+(2x+4)=-18
6x+6=-18
6x=-24
x=-4
therefore no.s are -8, -6, -4

2007-01-26 13:28:51 · answer #1 · answered by Anonymous · 1 1

a million)R: permit x be the smallest no. of the three E: x+x+2+x+4=183 S: 3x = 177 x = fifty 9 A: fifty 9, sixty one,sixty 3 2) R: permit x be the different no. E: x+3x=372 S: 4x =372 x = ninety 3 A: ninety 3, 279 3) R: permit x be the different no. E: x+x+3= 39 S: 2x = 36 x = 18 A: 18, 21 4) R: contemporary Age 4 yrs. in the past Rudy x+8 x+8-4 or only x+4 Carmen x x-4 E: x+4=2(x-4) S: x+4=2x-8 12 = x A: Rudy = 20 yrs. old Carmen= 12 yrs. old 5) R: contemporary Age Joey x-5 Tom x E: x+x-5=33 S: 2x =38 x =19 A: Joey = 14 yrs. old 6) R: contemporary Age Marco x+2+4 (or only x+6) Anne x+2 Diane x E: x+6+x+2+x=sixty two S: 3x =fifty 4 x =18 A: Marco = 24 yrs. old Anne = 20 yrs. old Diane = 18 yrs. old Legend: R: illustration E: Equation S: answer A: answer/s :) :) :)

2016-12-16 14:29:13 · answer #2 · answered by Anonymous · 0 0

Numerical data:
1. x+2
2. x+4
3. x+6

First: combine the expressions & equal them to "-18"...

x + 2 + x + 4 + x + 6 = - 18
3x + 12 = - 18

Sec: subtract "12" from both sides...

3x + 12 - 12 = - 18 - 12
3x = - 30

Third: isolate "x" on one side > divide both terms by "3"...

3x/3 = - 30/3
x = - 10

Fourth: replace "-10" with the x-variavles in the expressions...

1. x+2
- 10 + 2
= - 8

2. x+4
- 10 + 4
= - 6

3. x+6
- 10 + 6
= - 4

SOlutions: - 4, -6, and -8

2007-01-26 14:38:47 · answer #3 · answered by ♪♥Annie♥♪ 6 · 1 0

Make the smallest of the three integers (x-2). The other two integers would then be x and (x+2). I'll assume x to be even, as three odd integers can't add up to an even number like -18. Now just set the sum of them equal to -18.

(x-2)+x+(x+2)= -18
3x = -18
x = -6

The three even integers are -8, -6, and -4, which indeed add up to -18.

2007-01-26 14:43:46 · answer #4 · answered by Kyrix 6 · 1 0

lets just start by letting the first of the 3 intergers be called "n"

the next consecutive even integer would be n+2, right?

the next one after that would be n+2+2.

So, lets make the equation where these three sum to = -18.
n+ (n+2) + (n+2+2) =-18
n+n+n+2+2+2=-18
3n+6=-18
3n=-24
n=-8

so, the first one is -8, the next -6 and the last -4
-8,-6,-4

lets check, consecutive even integers? yep
sum to equal -18? -8-6-4=-18, yep!

go for it

2007-01-26 13:31:53 · answer #5 · answered by enginerd 6 · 1 2

Three consecutive integers numbers:
n + (n -1) + (n - 2) = -18
3n = -18 + 3
3n = -15
n = -15 : 3
n = -5
Ans: The nrs are: -7, -6, -5.
><

2007-01-26 13:34:50 · answer #6 · answered by aeiou 7 · 0 2

x + (x + 2) + (x + 4) = -18
x + x + 2 + x + 4 = -18
3x + 6 = -18
3x = -24
x = -8

ANS : -8, -6, and -4

2007-01-26 14:25:49 · answer #7 · answered by Sherman81 6 · 1 0

if n is the first integer, then n+2 would be the second and n+3 the third, so solve for (n) + (n+2) + (n+4) = 18

2007-01-26 13:28:40 · answer #8 · answered by themountainviewguy 4 · 0 3

-8,-6,-4

(-8) + (-6) + (-4) = -18

2007-01-26 13:30:53 · answer #9 · answered by ? 4 · 0 1

-4,-6,-8

2007-01-26 14:54:53 · answer #10 · answered by futureastronaut1 3 · 1 0

find the following sum 18+(-9)

2015-03-18 12:48:17 · answer #11 · answered by Gary1722000 2 · 0 0

fedest.com, questions and answers